Chemical constituents and antiproliferative activity of Eleusine indica (L.) Gaertn. - Syahirah Sukor,; Zuriati Zahari,; Norina Rahim,; Juliana Yusoff,; Fatimah Salim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Eleusine indica, locally known as ‘rumput sambau’ is widely used by traditional practitioners in many parts of the world to treat various ailments including sprained muscle, asthma, black jaundice, stomach pain, diarrhea, convulsions, and those related to infection such as malaria, influenza, dysentery as well as pneumonia. The plant has been reported to possess a wide array of biological activities, which were antioxidant, anti-inflammatory, antimicrobial, antidiabetic, antipyretic, antiplasmodial, antiviral, hepatoprotective, and urolithiasis. Despite all the reported traditional uses and biological activities, not many chemical constituents have been isolated from the plant. In this work, E. indica methanolic and hexane extracts were assessed for their anti-proliferative activities against human liver cancer (HepG2) and African green monkey kidney epithelial normal (Vero) cell lines through 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay. Although both extracts were considered to be not active on both cell lines with an IC50 of 91.02 ± 5.74 and 85.30 ± 3.03 μg/mL, and CC50 of >1000 and 639.39 ± 13.97 μg/mL, they were nevertheless more selective towards HepG2 cancer cells compared to the Vero normal cells with selectivity indexes (SI) of 10.99 and 7.50, respectively. Chemical profiling of the extracts on ultra-high performance liquid chromatography (UHPLC) coupled with a diode array detector showed a mixture of different complexity and polarities of compounds. Further isolation and purification on the hexane extract afforded β-sitosterol and stigmasterol, while the methanolic extract yielded loliolide, a benzofuran type of compound. Loliolide has been previously reported to exhibit antitumor activity, which could correlate to the higher antiproliferative selectivity against HepG2 cancer cell line of the methanolic compared to the hexane extracts. This is the first report on the isolation of β-sitosterol, stigmasterol, and loliolide from E. indica.